APAP-Induced IκBβ/NFκB Signaling Drives Hepatic Il6 Expression and Associated Sinusoidal Dilation. (2nd November 2021) - Sherlock, Laura G; Balasubramaniyan, Durganili; Zheng, Lijun; Grayck, Maya; McCarthy, William C; De Dios, Robert C; Zarate, Miguel A; Orlicky, David J; De Dios, Robyn; Wright, Clyde J
Abstract: Acetaminophen (APAP) overdose results in high morbidity and mortality, with limited treatment options. Increased understanding of the cellular signaling pathways activated in response to toxic APAP exposure is needed to provide insight into novel therapeutic strategies. Toxic APAP exposure induces hepatic nuclear factor kappa B (NFκB) activation. NFκB signaling has been identified to mediate the proinflammatory response but also induces a prosurvival and regenerative response. It is currently unknown whether potentiating NFkB activation would be injurious or advantageous after APAP overdose. The NFκB inhibitory protein beta (IκBβ) dictates the duration and degree of the NFκB response following exposure to oxidative injuries. Thus, we sought to determine whether IκBβ/NFκB signaling contributes to APAP-induced hepatic injury. At late time points (24 h) following toxic APAP exposures, mice expressing only IκBβ knock-in mice (AKBI mice) exhibited increased serologic evidence of hepatic injury. This corresponded with increased histologic injury, specifically related to sinusoidal dilatation. When compared with wild type mice, AKBI mice demonstrated sustained hepatic nuclear translocation of the NFκB subunits p65 and p50, and enhanced NFκB target gene expression. This included increased expression of interleukin-6 (Il-6), a known contributor to hepatic sinusoidal dilation. This transcriptional response corresponded with increased plasma protein content of Il-6, as well as increased activation of signal transducer and activator of transcription 3.